2010
DOI: 10.1038/hr.2010.245
|View full text |Cite
|
Sign up to set email alerts
|

Hypertensive crisis: clinical–epidemiological profile

Abstract: Hypertensive crisis (HC) stands out as one type of acute elevation in blood pressure (BP) and can manifest as hypertensive emergency (HE-with target-organ damage (TOD)) or hypertensive urgency (HU-without TOD), usually accompanied by levels of diastolic BP X120 mm Hg. The aim of this study was to characterize the clinical-epidemiological profile of HC over the course of 1 year in a university reference hospital and perform a review of the literature. The study was a cross-sectional study, conducted over a peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
45
8
18

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(83 citation statements)
references
References 25 publications
12
45
8
18
Order By: Relevance
“…This condition increases the prevalence of HC, probably being responsible for the large difference in the prevalence found in the literature (0.45 to 27.5%) [2]. Although no significant difference was found between the prevalence of DM or previous antidiabetic treatment in our sample, other study [3] showed a higher prevalence of DM among individuals admitted with HE when compared with those with HU.…”
Section: Dear Editormentioning
confidence: 42%
See 1 more Smart Citation
“…This condition increases the prevalence of HC, probably being responsible for the large difference in the prevalence found in the literature (0.45 to 27.5%) [2]. Although no significant difference was found between the prevalence of DM or previous antidiabetic treatment in our sample, other study [3] showed a higher prevalence of DM among individuals admitted with HE when compared with those with HU.…”
Section: Dear Editormentioning
confidence: 42%
“…First, we would like to congratulate the authors for their excellent work, and then make some comments regarding the issue addressed and compare their results with those published recently by our group [2]. We found a prevalence of HC that corresponded to 0.45% of all emergencies and 2.0% of clinical emergencies in our service, which is responsible for providing secondary and tertiary care for a population of approximately 1.5 million inhabitants.…”
Section: Dear Editormentioning
confidence: 85%
“…1–3 Short term risk factors – or triggers – of acute ischemic stroke include hypertensive crisis 4 , alcohol abuse 5 , and may include acute infection. 5 Herein, we explore the relationship between hospitalization with infection and short-term stroke risk.…”
Section: Introductionmentioning
confidence: 99%
“…25%-35% adults over the world have hypertension. There are over 972 million hypertension patients, of which 60%-70% are over 70 years old [2][3].…”
Section: Introductionmentioning
confidence: 99%